Research on the Upper Secondary Education Provided by Private Institutions in Ho Chi Minh City, Vietnam - THI MAI PHUONG LE (International Journal of Multidisciplinary Research and Studies, 2023)
Social groups, socio-professional groups, economic groups, and individuals can all create private educational institutions with the approval of the appropriate governmental bodies. The non-state budget is where private schools acquire the money they need to invest in infrastructure and keep the lights on. The primary goal of this research is to conduct an empirical evaluation of private high schools in Ho Chi Minh City, Vietnam. The author used information from completed research as secondary sources. The findings of the study indicate that I the number of students in each class and the number of teachers at each school; (ii) the number of administrative staff members and teachers; (iii) the number of classrooms and other learning spaces; and (iv) the actual implementation of various educational activities, such as the creation of action plans and the delivery of lessons on topics such as career preparation and extracurriculars. Some suggestions are made to enhance private postsecondary education in light of the results.